Special environment-friendly anti-seepage and compression-resistant polymer coating for water conservancy and preparation method thereof

Through the combination of silicone modified epoxy resin, modified glass flakes and modified nitrile rubber, the problems of insufficient corrosion resistance, penetration resistance and curing rate of water conservancy engineering coatings are solved, and the performance of the coating is improved, which is suitable for water conservancy. High performance coating requirements in engineering.

CN119242136AInactive Publication Date: 2025-01-03ZHONGBO (QINHUANGDAO) NEW MATERIAL TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411614883.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The solvent-free epoxy resin polymer coatings in existing water conservancy projects have shortcomings in corrosion resistance, permeability, UV resistance and curing rate, especially the low binding force of glass flakes and epoxy resin, and benzotrinitrogen Poor azole stability, poor UV resistance of nitrile rubber and slow curing rate of aromatic primary amines.

Method used

Using silicone modified epoxy resin, modified glass flakes and modified nitrile rubber, the glass flakes are surface activated and combined with benzotriazole to increase its stability in the coating, and in nitrile rubber The introduction of thiophene rings and aromatic primary amines improves the permeability, corrosion resistance and curing rate of the paint.

Benefits of technology

It significantly improves the permeability, corrosion resistance, compressive strength and curing rate of the coating, and enhances its application performance in water conservancy projects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an environment-friendly anti-seepage and compression-resistant polymer coating special for water conservancy and a preparation method thereof, and relates to the field of water conservancy project coatings. The coating is prepared from the following raw materials in parts by weight: 40 to 50 parts of organic silicon modified epoxy resin, 30 to 40 parts of reactive diluent, 10 to 15 parts of modified glass flake, 8 to 10 parts of modified nitrile rubber, 0.3 to 0.5 part of defoaming agent, 0.5 to 1.0 part of flatting agent, 1 to 2 parts of dispersing agent and 2 to 3 parts of pigment. The modified glass flakes are obtained by loading benzotriazole and alkane long chains in glass flakes. The modified nitrile rubber is obtained by introducing aromatic primary amine, tertiary amine, thiophene ring and the like into nitrile rubber. The polymer coating disclosed by the invention has excellent corrosion resistance, impermeability, pressure resistance and weather resistance, high curing rate and high environmental protection property, and is worthy of popularization and application in the field of water utilization coatings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of water conservancy engineering coatings, and in particular to an environmentally friendly anti-seepage and anti-pressure polymer coating special for water conservancy and a preparation method thereof. Background Art

[0002] The environment of water conservancy projects is generally characterized by high humidity, high rainfall, and high sand content in the water, which can easily cause corrosion of the dam's steel structure. Therefore, a coating system with excellent anti-corrosion performance should be used during the construction of water conservancy projects to increase the service life of the steel structure. Generally, steel structural parts in water conservancy projects cannot be transported out during inspection and maintenance, so manual rust removal is required on site, that is, anti-corrosion coating is applied under low surface treatment conditions, which greatly increases the anti-corrosion performance requirements for the coating.

[0003] The molecular structure of epoxy resin makes epoxy coatings have great advantages in bonding and corrosion resistance and are widely used in water conservancy projects. Compared with solvent-based epoxy resin polymer coatings, solvent-free epoxy resin polymer coatings reduce the solvent volatilization of the coating during the curing process and can also reduce the curing shrinkage of epoxy materials, which is beneficial to the mechanical properties and corrosion resistance of epoxy coatings and has high environmental protection.

[0004] In the prior art, glass flakes are arranged parallel to each other and overlapped inside the coating, which can form a barrier to prevent the diffusion of corrosive media and prolong the time for corrosive media to penetrate into the substrate, thereby improving the corrosion resistance and anti-penetration performance of epoxy resin coatings. However, the bonding force between glass flakes and epoxy resin is relatively low. Benzotriazole is widely used and has a good inhibitory effect on the corrosion behavior of carbon steel in hydrochloric acid corrosive media. It is a good corrosion inhibitor and is widely used in coating additives, preservatives, etc. However, directly adding benzotriazole small molecules to the coating cannot stably exert its anti-corrosion performance.

[0005] Carboxyl-terminated liquid nitrile rubber has good adhesion and fluidity, and is often used to toughen epoxy resins and improve the impact resistance of epoxy coatings. However, nitrile rubber contains double bonds in its molecular chain, so it is easily damaged by aging effects such as ultraviolet rays, oxygen, and ozone. Nitrile rubber has poor ultraviolet resistance, so its use in epoxy resin coatings is limited. In addition, the curing process of epoxy resins requires heating when using aromatic primary amine curing agents, and the curing rate is slow, which limits its use in epoxy resin polymer coatings.

[0006] Therefore, suitable modification methods are needed to improve the dispersibility of glass flakes and the stability of benzotriazole, enhance the UV resistance of nitrile rubber and the curing rate of aromatic primary amine curing agent, so as to improve the anti-penetration, corrosion resistance, UV resistance and curing rate of solvent-free epoxy resin polymer coatings, which is important and necessary. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides an environmentally friendly anti-seepage and anti-pressure polymer coating specially used for water conservancy and a preparation method thereof.

[0008] The purpose of the present invention can be achieved through the following technical solutions: A special environmentally friendly anti-seepage and anti-pressure polymer coating for water conservancy, comprising the following raw materials in parts by weight: 40-50 parts of organosilicon-modified epoxy resin, 30-40 parts of reactive diluent, 10-15 parts of modified glass flakes, 8-10 parts of modified nitrile rubber, 0.3-0.5 parts of defoaming agent, 0.5-1.0 parts of leveling agent, 1-2 parts of dispersant, and 2-3 parts of pigment; The active diluent is selected from one of phenyl glycidyl ether, allyl glycidyl ether and butyl glycidyl ether; the defoamer is an organosilicon defoamer; the leveling agent is a polyacrylate leveling agent; the dispersant is sodium dodecyl sulfate; the pigment is selected from one of titanium dioxide, chrome yellow, iron red and ultramarine; The preparation of the environmentally friendly anti-seepage and anti-pressure polymer coating for water conservancy includes the following steps: The organosilicon-modified epoxy resin and the active diluent are stirred and mixed at 500-600 r / min for 5-10 min, and then the speed is reduced to 100-200 r / min, and a defoamer, a leveling agent, a dispersant and a pigment are added, and the mixture is stirred and mixed at 500-600 r / min for 5-10 min, and then the speed is reduced to 200-300 r / min, and modified glass flakes are added, and the mixture is stirred and mixed at 800-1000 r / min for 35-45 min, and then the speed is reduced to 200-300 r / min, and modified nitrile rubber is added, and the mixture is stirred and mixed at 600-700 r / min for 20-30 min to obtain an environmentally friendly anti-seepage and anti-pressure polymer coating for water conservancy.

[0009] The preparation of the modified glass flakes comprises the following steps: Step A1: Stir and mix glass flakes, xylene and stannous octoate at room temperature for 30-40 minutes to obtain solution 1; then add diisocyanate to xylene and ultrasonically disperse for 15-20 minutes, then add it dropwise to solution 1 through a constant pressure dropping funnel in a protective gas atmosphere, and then stir and react at 140-150° C. for 4-5 hours to obtain surface-activated glass flakes; then add the surface-activated glass flakes and nitro-containing benzotriazole to ethyl acetate, and stir at room temperature for 2-3 hours to obtain a nitro product; Further, in solution 1, the amount ratio of glass flakes, xylene, and stannous octoate is 20-23g:300-320mL:0.05-0.07g; the diisocyanate is hexamethylene diisocyanate, and the amount ratio of diisocyanate, xylene, and solution 1 is 10-12g:100-120mL:355-365mL; ​​the nitro-containing benzotriazole is 4-nitro-1H-1,2,3-benzotriazole, and the amount ratio of surface-activated glass flakes, nitro-containing benzotriazole, and ethyl acetate is 15-17g:20-23g:75-85mL; the glass flakes and xylene are both used after dehydration, and the dehydration method of the glass flakes is: the glass flakes are placed at 100-110°C and dried for 4-5h; the dehydration method of xylene is: xylene is added to 3A molecular sieves and stirred for 1-1.5h and then filtered; During the reaction of step A1, one isocyanate group of the diisocyanate reacts with the silanol group on the surface of the glass flakes, and the other isocyanate group is distributed on the surface of the glass flakes to obtain surface-activated glass flakes; the isocyanate group of the surface-activated glass flakes reacts with the secondary amino group in 4-nitro-1H-1,2,3-benzotriazole to obtain a nitro product; Step A2: Add the nitro product to toluene, raise the temperature to 45-50°C, start reflux stirring, then add sodium dithionite, and reflux stirring to react for 1-1.5h to obtain the amino product; Further, the usage ratio of nitro product, toluene, and sodium dithionite is 18-20 g: 80-90 mL: 12-14 g; During the reaction of step A2, the nitro group of the nitro product is reduced to an amino group to obtain an amino product; Step A3: adding the amino product and potassium carbonate to dimethyl sulfoxide and stirring to obtain a mixed solution 1, then adding lauroyl chloride to dimethyl sulfoxide and stirring to obtain a mixed solution 2, adding the mixed solution 2 dropwise to the mixed solution 1 under an ice-water bath, and after the addition is complete, heating to 40-45° C., stirring to react for 8-10 hours, and distilling under reduced pressure to obtain modified glass flakes; Further, the dosage ratio of the amino product, potassium carbonate and dimethyl sulfoxide in the mixed solution 1 is 6-8 g: 0.5-1.0 g: 40-50 mL; the dosage ratio of lauroyl chloride and dimethyl sulfoxide in the mixed solution 2 is 5.5-6.5 g: 20-30 mL; the dosage ratio of the mixed solution 1 and the mixed solution 2 is 50-60 mL: 25-35 mL; During the reaction of step A3, lauroyl chloride reacts with the amino product to obtain modified glass flakes.

[0010] The modified nitrile rubber is prepared by the following steps: Step B1: Add 4-amino-N,N-dimethyl-3-nitroaniline and potassium carbonate to dimethyl sulfoxide and stir to obtain a mixed solution a, then add 4-pentenoyl chloride to dimethyl sulfoxide and stir to obtain a mixed solution b, and dropwise add the mixed solution b to the mixed solution a in an ice-water bath. After the dropwise addition is completed, the temperature is raised to 40-45° C., the reaction is stirred for 8-10 hours, and the double bond product is obtained by distillation under reduced pressure; Further, the dosage ratio of 4-amino-N,N-dimethyl-3-nitroaniline, potassium carbonate and dimethyl sulfoxide in the mixed solution a is 0.1-0.15 mol: 0.02-0.04 mol: 70-80 mL; the dosage ratio of 4-pentenoyl chloride and dimethyl sulfoxide in the mixed solution b is 0.15-0.17 mol: 30-40 mL; the dosage ratio of the mixed solution a and the mixed solution b is 75-85 mL: 40-50 mL; During the reaction of step B1, 4-pentenoyl chloride reacts with the primary amino group of 4-amino-N,N-dimethyl-3-nitroaniline to obtain a double bond product containing a tertiary amine and a nitro group; Step B2: Add the double bond product to dichloromethane, stir for 30-40 minutes, then add 3-chloroperoxybenzoic acid, stir and react at room temperature for 5-6 hours to obtain an epoxy product; in a protective gas atmosphere, add 2,5-thiophene dicarboxylic acid to toluene, heat to 50-60°C, add pyridine, start stirring, then add the epoxy product, stir and react for 10-12 hours, then heat to 110-120°C, stir for 1-2 hours to obtain a hydroxyl product; Further, the usage ratio of the double bond product, dichloromethane, and 3-chloroperoxybenzoic acid is 30-32 g: 80-90 mL: 18-20 g; the usage ratio of 2,5-thiophenedicarboxylic acid, toluene, pyridine, and epoxy product is 20-23 g: 180-200 mL: 0.2-0.25 mol: 68-70 g; During the reaction of step B2, the double bond of the double bond product is oxidized to an epoxy group to obtain an epoxy product; the carboxyl group of 2,5-thiophenedicarboxylic acid reacts with the epoxy group of the epoxy product to form a hydroxyl product; Step B3: Add carboxylated nitrile rubber to DMF, add dichlorothionyl under stirring, reflux and stir at 50-60°C for 6-8h to obtain an acyl chloride product; stir and mix the hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide to obtain a mixed solution c; add the acyl chloride product to dimethyl sulfoxide to obtain a mixed solution d, slowly drop the mixed solution d into the mixed solution c in an ice-water bath, raise the temperature to 40-45°C after the dropwise addition is complete, stir and react at a constant temperature for 8-10h, then raise the temperature to 100-110°C, continue stirring for 1-2h, and distill under reduced pressure to obtain a nitro product; Further, the dosage ratio of carboxylated nitrile rubber, DMF, and dichlorothionyl is 36-40 g: 100-110 mL: 12-14 g; the dosage ratio of hydroxyl product, pyridine, triethylamine, and dimethyl sulfoxide in mixed solution c is 88-90 g: 4-6 mL: 15-20 mL: 160-170 mL; the dosage ratio of acyl chloride product and dimethyl sulfoxide in mixed solution d is 42-44 g: 90-100 mL; the dosage ratio of mixed solution c and mixed solution d is 170-180 mL: 100-110 mL; During the reaction of step B3, the carboxyl group of the carboxylated nitrile rubber reacts with thionyl chloride to generate an acyl chloride product; the acyl chloride product reacts with the alcoholic hydroxyl group of the hydroxyl product to generate a nitro product; Step B4: adding the nitro product to toluene, heating to 50-60° C., starting reflux stirring, then adding sodium dithionite, and then reflux stirring to react for 3-3.5 hours to obtain modified nitrile rubber; Further, the usage ratio of nitro product, toluene, and sodium dithionite is 65-70 g: 200-210 mL: 35-37 g; During the reaction of step B4, the nitro group of the nitro product is reduced to an amino group to obtain a modified nitrile rubber containing a thiophene ring, an aromatic primary amine and a tertiary amine.

[0011] Beneficial effects of the invention: The invention discloses a special environmentally friendly anti-seepage and anti-pressure polymer coating for water conservancy, comprising raw materials such as silicone-modified epoxy resin, reactive diluent, modified glass flakes, modified nitrile rubber, etc. The special environmentally friendly anti-seepage and anti-pressure polymer coating belongs to solvent-free epoxy resin raw materials and is highly environmentally friendly.

[0012] The synthesized modified glass flakes are obtained by activating glass flakes by reacting with diisocyanate, and then reacting with nitro-containing benzotriazole and lauroyl chloride, thereby loading benzotriazole and alkane long chains in the glass flakes. After surface modification, the hydrophilicity of the glass flakes is weakened, and the compatibility and dispersibility with epoxy resin are enhanced. A dense parallel overlapping arrangement can be formed in the coating, which effectively improves the anti-permeability and anti-corrosion properties of the coating. The glass flakes can also make the epoxy resin have a higher hardness, thereby improving the compressive strength of the coating, thereby meeting the requirements of the compressive resistance of the coating; benzotriazole can form a stable complex with metal substrates such as steel plates, forming a protective film on the metal surface to prevent the approach of corrosive media, and loading it on the glass flakes to enhance its stability in the coating. Benzotriazole and glass flakes produce intramolecular synergy, which can produce excellent anti-corrosion performance; the lauroyl chloride used is a derivative of the natural fatty acid lauric acid, which enhances the environmental protection of the coating.

[0013] The synthesized modified nitrile rubber is obtained by grafting tertiary amines, aromatic primary amines, thiophene rings, etc. into carboxylated nitrile rubber through the reaction of carboxylated nitrile rubber. The thiophene ring can effectively absorb ultraviolet energy and convert it into low-energy heat energy and release it, thereby reducing the aging effect of ultraviolet rays on nitrile rubber. The thiophene ring grafted into carboxylated nitrile rubber is not easy to migrate and fail, which not only gives nitrile rubber ultraviolet resistance, but also improves the ultraviolet resistance of the coating, thereby enhancing the weather resistance of the coating; aromatic primary amines are grafted into carboxylated nitrile rubber, so that the modified nitrile rubber has the ability to cure epoxy resins, and the introduced tertiary amine group has a catalytic effect on the aromatic primary amine curing epoxy resin, thereby accelerating the curing rate of the coating.

[0014] Therefore, the environmentally friendly water conservancy-specific anti-seepage and anti-pressure polymer coating of the present invention has a faster curing rate and excellent corrosion resistance, anti-seepage and anti-pressure properties, and weather resistance, and is worthy of being promoted and used in water conservancy projects. DETAILED DESCRIPTION

[0015] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0016] Example 1 A modified glass flake, the preparation of which comprises the following steps: Step A1: Mix glass flakes (supplier: Lingshou County Laipeng Mineral Products Business Department, 40 mesh), xylene, and stannous octoate at room temperature and stir for 30 minutes to obtain solution 1; then add hexamethylene diisocyanate to xylene and ultrasonically disperse for 15 minutes, then add it dropwise to solution 1 through a constant pressure dropping funnel in a nitrogen atmosphere, and then stir and react at 140°C for 4 hours to obtain surface-activated glass flakes; then add surface-activated glass flakes and 4-nitro-1H-1,2,3-benzotriazole to ethyl acetate and stir at room temperature for 2 hours to obtain a nitro product; in solution 1, glass flakes The usage ratio of flakes, xylene and stannous octoate is 20g:300mL:0.05g; the usage ratio of hexamethylene diisocyanate, xylene and solution 1 is 10g:100mL:355mL; the usage ratio of surface activated glass flakes, 4-nitro-1H-1,2,3-benzotriazole and ethyl acetate is 15g:20g:75mL; the glass flakes and xylene are both used after dehydration, and the dehydration method of the glass flakes is: placing the glass flakes at 100°C and drying for 4h; the dehydration method of xylene is: adding xylene to 3A molecular sieves, stirring for 1h and then filtering; Step A2: Add the nitro product to toluene, heat to 45°C, start reflux stirring, then add sodium dithionite, and reflux stirring for 1 hour to obtain the amino product; the amount ratio of the nitro product, toluene, and sodium dithionite is 18g:80mL:12g; Step A3: Add the amino product and potassium carbonate to dimethyl sulfoxide, stir and mix to obtain a mixed solution 1, then add lauroyl chloride to dimethyl sulfoxide, stir and mix to obtain a mixed solution 2, and add the mixed solution 2 dropwise to the mixed solution 1 under an ice-water bath. After the addition is complete, the mixture is heated to 40°C, stirred to react for 8 hours, and distilled under reduced pressure to obtain modified glass flakes; the amount ratio of the amino product, potassium carbonate, and dimethyl sulfoxide in the mixed solution 1 is 6g:0.5g:40mL; the amount ratio of lauroyl chloride and dimethyl sulfoxide in the mixed solution 2 is 5.5g:20mL; the amount ratio of the mixed solution 1 to the mixed solution 2 is 50mL:25mL.

[0017] Example 2 A modified glass flake, the preparation of which comprises the following steps: Step A1: Mix glass flakes (supplier: Lingshou County Laipeng Mineral Products Business Department, 40 mesh), xylene, and stannous octoate at room temperature and stir for 35 minutes to obtain solution 1; then add hexamethylene diisocyanate to xylene and ultrasonically disperse for 17 minutes, then add it dropwise to solution 1 through a constant pressure dropping funnel in a protective gas atmosphere, and then stir and react at 145°C for 4.5 hours to obtain surface-activated glass flakes; then add surface-activated glass flakes and 4-nitro-1H-1,2,3-benzotriazole to ethyl acetate and stir at room temperature for 2.5 hours to obtain a nitro product; in solution 1, glass The dosage ratio of flakes, xylene, and stannous octoate is 21g:310mL:0.06g; the dosage ratio of hexamethylene diisocyanate, xylene, and solution 1 is 11g:110mL:360mL; the dosage ratio of surface-activated glass flakes, 4-nitro-1H-1,2,3-benzotriazole, and ethyl acetate is 16g:21g:80mL; the glass flakes and xylene are both used after dehydration, and the dehydration method of the glass flakes is: the glass flakes are placed at 105°C and dried for 4.5h; the dehydration method of xylene is: xylene is added to 3A molecular sieves, stirred for 1.2h, and then filtered; Step A2: Add the nitro product to toluene, heat to 47°C, start reflux stirring, then add sodium dithionite, and reflux stirring to react for 1.3 hours to obtain the amino product; the amount ratio of the nitro product, toluene, and sodium dithionite is 19g:85mL:13g; Step A3: Add the amino product and potassium carbonate to dimethyl sulfoxide, stir and mix to obtain a mixed solution 1, then add lauroyl chloride to dimethyl sulfoxide, stir and mix to obtain a mixed solution 2, and add the mixed solution 2 dropwise to the mixed solution 1 under an ice-water bath. After the addition is complete, heat the mixture to 42°C, stir and react for 9 hours, and distill under reduced pressure to obtain modified glass flakes; the amount ratio of the amino product, potassium carbonate, and dimethyl sulfoxide in the mixed solution 1 is 7g:0.8g:45mL; the amount ratio of lauroyl chloride and dimethyl sulfoxide in the mixed solution 2 is 6.0g:25mL; the amount ratio of the mixed solution 1 to the mixed solution 2 is 55mL:30mL.

[0018] Example 3 A modified glass flake, the preparation of which comprises the following steps: Step A1: Mix glass flakes (supplier: Lingshou County Laipeng Mineral Products Business Department, 40 mesh), xylene, and stannous octoate at room temperature and stir for 40 minutes to obtain solution 1; then add hexamethylene diisocyanate to xylene and ultrasonically disperse for 20 minutes, then add it dropwise to solution 1 through a constant pressure dropping funnel in a protective gas atmosphere, and then stir and react at 150°C for 5 hours to obtain surface-activated glass flakes; then add surface-activated glass flakes and 4-nitro-1H-1,2,3-benzotriazole to ethyl acetate and stir at room temperature for 3 hours to obtain a nitro product; in solution 1, glass flakes The usage ratio of flakes, xylene and stannous octoate is 23g:320mL:0.07g; the usage ratio of hexamethylene diisocyanate, xylene and solution 1 is 12g:120mL:365mL; ​​the usage ratio of surface activated glass flakes, 4-nitro-1H-1,2,3-benzotriazole and ethyl acetate is 17g:23g:85mL; the glass flakes and xylene are both used after dehydration, and the dehydration method of the glass flakes is: placing the glass flakes at 110°C and drying for 5h; the dehydration method of xylene is: adding xylene to 3A molecular sieves, stirring for 1.5h and filtering; Step A2: Add the nitro product to toluene, heat to 50°C, start reflux stirring, then add sodium dithionite, and reflux stirring to react for 1.5 hours to obtain the amino product; the amount ratio of the nitro product, toluene, and sodium dithionite is 20g:90mL:14g; Step A3: Add the amino product and potassium carbonate to dimethyl sulfoxide, stir and mix to obtain a mixed solution 1, then add lauroyl chloride to dimethyl sulfoxide, stir and mix to obtain a mixed solution 2, and add the mixed solution 2 dropwise to the mixed solution 1 under an ice-water bath. After the addition is complete, heat the mixture to 45°C, stir and react for 10 hours, and distill under reduced pressure to obtain modified glass flakes; the amount ratio of the amino product, potassium carbonate, and dimethyl sulfoxide in the mixed solution 1 is 8g:1.0g:50mL; the amount ratio of lauroyl chloride and dimethyl sulfoxide in the mixed solution 2 is 6.5g:30mL; the amount ratio of the mixed solution 1 to the mixed solution 2 is 60mL:35mL.

[0019] Example 4 A modified nitrile rubber, the preparation of which comprises the following steps: Step B1: Add 4-amino-N,N-dimethyl-3-nitroaniline and potassium carbonate to dimethyl sulfoxide, stir and mix to obtain a mixed solution a, then add 4-pentenoyl chloride to dimethyl sulfoxide, stir and mix to obtain a mixed solution b, add the mixed solution b dropwise to the mixed solution a in an ice-water bath, after the dropwise addition is complete, heat to 40°C, stir and react for 8 hours, and distill under reduced pressure to obtain a double bond product; the amount ratio of 4-amino-N,N-dimethyl-3-nitroaniline, potassium carbonate, and dimethyl sulfoxide in the mixed solution a is 0.1 mol: 0.02 mol: 70 mL; the amount ratio of 4-pentenoyl chloride and dimethyl sulfoxide in the mixed solution b is 0.15 mol: 30 mL; the amount ratio of the mixed solution a to the mixed solution b is 75 mL: 40 mL; Step B2: Add the double bond product to dichloromethane, stir for 30 minutes, then add 3-chloroperoxybenzoic acid, stir and react at room temperature for 5 hours to obtain an epoxy product; in a protective gas atmosphere, add 2,5-thiophene dicarboxylic acid to toluene, heat to 50°C, add pyridine, start stirring, then add the epoxy product, stir and react for 10 hours, then heat to 110°C, stir for 1 hour to obtain a hydroxyl product; the dosage ratio of the double bond product, dichloromethane, and 3-chloroperoxybenzoic acid is 30g:80mL:18g; the dosage ratio of 2,5-thiophene dicarboxylic acid, toluene, pyridine, and epoxy product is 20g:180mL:0.2mol:68g; Step B3: Add carboxylated nitrile rubber (supplier: Wuhan Jixinyibang Biotechnology Co., Ltd.) to DMF, add dichlorothionyl under stirring, reflux and react at 50°C for 6 hours to obtain an acyl chloride product; stir and mix the hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide to obtain a mixed solution c; add the acyl chloride product to dimethyl sulfoxide to obtain a mixed solution d, slowly drop the mixed solution d into the mixed solution c in an ice water bath, raise the temperature to 40°C after the addition is complete, and stir and react at a constant temperature for 8 hours. Then the temperature was raised to 100°C, stirring was continued for 1 hour, and the nitro product was obtained by distillation under reduced pressure; the dosage ratio of carboxylated nitrile rubber, DMF, and dichlorothionyl was 36g:100mL:12g; the dosage ratio of hydroxyl product, pyridine, triethylamine, and dimethyl sulfoxide in mixed solution c was 88g:4mL:15mL:160mL; the dosage ratio of acyl chloride product and dimethyl sulfoxide in mixed solution d was 42g:90mL; the dosage ratio of mixed solution c and mixed solution d was 170mL:100mL; Step B4: Add the nitro product to toluene, heat to 50°C, start reflux stirring, then add sodium dithionite, and reflux stirring to react for 3 hours to obtain modified nitrile rubber; the dosage ratio of the nitro product, toluene, and sodium dithionite is 65g:200mL:35g.

[0020] Example 5 A modified nitrile rubber, the preparation of which comprises the following steps: Step B1: Add 4-amino-N,N-dimethyl-3-nitroaniline and potassium carbonate to dimethyl sulfoxide, stir and mix to obtain a mixed solution a, then add 4-pentenoyl chloride to dimethyl sulfoxide, stir and mix to obtain a mixed solution b, add the mixed solution b dropwise to the mixed solution a in an ice-water bath, after the dropwise addition is complete, heat to 42° C., stir and react for 9 hours, and distill under reduced pressure to obtain a double bond product; the amount ratio of 4-amino-N,N-dimethyl-3-nitroaniline, potassium carbonate, and dimethyl sulfoxide in the mixed solution a is 0.13 mol: 0.03 mol: 75 mL; the amount ratio of 4-pentenoyl chloride and dimethyl sulfoxide in the mixed solution b is 0.16 mol: 35 mL; the amount ratio of the mixed solution a to the mixed solution b is 80 mL: 45 mL; Step B2: Add the double bond product to dichloromethane, stir for 35 minutes, then add 3-chloroperoxybenzoic acid, stir and react at room temperature for 5.5 hours to obtain an epoxy product; in a protective gas atmosphere, add 2,5-thiophene dicarboxylic acid to toluene, heat to 55°C, add pyridine, start stirring, then add the epoxy product, stir and react for 11 hours, then heat to 115°C, stir for 1.5 hours to obtain a hydroxyl product; the dosage ratio of the double bond product, dichloromethane, and 3-chloroperoxybenzoic acid is 31g:85mL:19g; the dosage ratio of 2,5-thiophene dicarboxylic acid, toluene, pyridine, and epoxy product is 21g:190mL:0.23mol:69g; Step B3: Carboxyl nitrile rubber (supplier: Wuhan Jixinyibang Biotechnology Co., Ltd.) was added to DMF, and dichlorothionyl was added under stirring, and the mixture was refluxed and stirred at 55°C for 7 hours to obtain an acyl chloride product; the hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide were stirred and mixed to obtain a mixed solution c; the acyl chloride product was added to dimethyl sulfoxide to obtain a mixed solution d, and the mixed solution d was slowly added dropwise to the mixed solution c in an ice water bath. After the addition was completed, the temperature was raised to 42°C, and the mixture was stirred at a constant temperature for 9 hours. Then the temperature was raised to 105°C, stirring was continued for 1.5h, and the nitro product was obtained by distillation under reduced pressure; the dosage ratio of carboxylated nitrile rubber, DMF, and dichlorothionyl was 38g:105mL:13g; the dosage ratio of hydroxyl product, pyridine, triethylamine, and dimethyl sulfoxide in mixed solution c was 89g:5mL:17mL:165mL; ​​the dosage ratio of acyl chloride product and dimethyl sulfoxide in mixed solution d was 43g:95mL; the dosage ratio of mixed solution c and mixed solution d was 175mL:105mL; Step B4: Add the nitro product to toluene, heat to 55°C, start reflux stirring, then add sodium dithionite, and reflux stirring to react for 3.2 hours to obtain modified nitrile rubber; the dosage ratio of the nitro product, toluene, and sodium dithionite is 67g:205mL:36g.

[0021] Example 6 A modified nitrile rubber, the preparation of which comprises the following steps: Step B1: Add 4-amino-N,N-dimethyl-3-nitroaniline and potassium carbonate to dimethyl sulfoxide, stir and mix to obtain a mixed solution a, then add 4-pentenoyl chloride to dimethyl sulfoxide, stir and mix to obtain a mixed solution b, add the mixed solution b dropwise to the mixed solution a in an ice-water bath, after the dropwise addition is completed, heat to 45° C., stir and react for 10 hours, and distill under reduced pressure to obtain a double bond product; the amount ratio of 4-amino-N,N-dimethyl-3-nitroaniline, potassium carbonate, and dimethyl sulfoxide in the mixed solution a is 0.15 mol: 0.04 mol: 80 mL; the amount ratio of 4-pentenoyl chloride and dimethyl sulfoxide in the mixed solution b is 0.17 mol: 40 mL; the amount ratio of the mixed solution a to the mixed solution b is 85 mL: 50 mL; Step B2: Add the double bond product to dichloromethane, stir for 40 minutes, then add 3-chloroperoxybenzoic acid, stir and react at room temperature for 6 hours to obtain an epoxy product; in a protective gas atmosphere, add 2,5-thiophene dicarboxylic acid to toluene, heat to 60°C, add pyridine, start stirring, then add the epoxy product, stir and react for 12 hours, then heat to 120°C, stir for 2 hours to obtain a hydroxyl product; the dosage ratio of the double bond product, dichloromethane, and 3-chloroperoxybenzoic acid is 32g:90mL:20g; the dosage ratio of 2,5-thiophene dicarboxylic acid, toluene, pyridine, and epoxy product is 23g:200mL:0.25mol:70g; Step B3: Add carboxylated nitrile rubber (supplier: Wuhan Jixinyibang Biotechnology Co., Ltd.) to DMF, add dichlorothionyl under stirring, reflux and stir at 60°C for 8 hours to obtain an acyl chloride product; stir and mix the hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide to obtain a mixed solution c; add the acyl chloride product to dimethyl sulfoxide to obtain a mixed solution d, slowly drop the mixed solution d into the mixed solution c in an ice water bath, raise the temperature to 45°C after the addition is complete, and stir and react at a constant temperature for 10 hours. Then the temperature was raised to 110°C, stirring was continued for 2 hours, and the nitro product was obtained by distillation under reduced pressure; the dosage ratio of carboxylated nitrile rubber, DMF, and dichlorothionyl was 40g:110mL:14g; the dosage ratio of hydroxyl product, pyridine, triethylamine, and dimethyl sulfoxide in mixed solution c was 90g:6mL:20mL:170mL; the dosage ratio of acyl chloride product and dimethyl sulfoxide in mixed solution d was 44g:100mL; the dosage ratio of mixed solution c and mixed solution d was 180mL:110mL; Step B4: Add the nitro product to toluene, heat to 60°C, start reflux stirring, then add sodium dithionite, and reflux stirring to react for 3.5 hours to obtain modified nitrile rubber; the dosage ratio of the nitro product, toluene, and sodium dithionite is 70g:210mL:37g.

[0022] Example 7 A water conservancy-specific environmentally friendly anti-seepage and anti-pressure polymer coating, comprising the following raw materials in parts by weight: 40 parts of silicone-modified epoxy resin, 30 parts of reactive diluent, 10 parts of modified glass flakes, 8 parts of modified nitrile rubber, 0.3 parts of defoaming agent, 0.5 parts of leveling agent, 1 part of dispersant, and 2 parts of pigment; The active diluent is phenyl glycidyl ether; the defoamer is silicone defoamer DF-102 (supplier: Dongguan Defeng Defoamer Co., Ltd.); the leveling agent is polyacrylate leveling agent BYK358N; the dispersant is sodium dodecyl sulfate; and the pigment is titanium dioxide; The preparation of the environmentally friendly anti-seepage and anti-pressure polymer coating for water conservancy includes the following steps: The organosilicon-modified epoxy resin and the active diluent are stirred and mixed at 500 r / min for 5 min, then the speed is reduced to 100 r / min and a defoamer, a leveling agent, a dispersant and a pigment are added, and the mixture is stirred and mixed at 500 r / min for 5 min. Then the speed is reduced to 200 r / min and the modified glass flakes obtained in Example 1 are added, and the mixture is stirred and mixed at 800 r / min for 35 min. Then the speed is reduced to 200 r / min and the modified nitrile rubber obtained in Example 4 is added, and the mixture is stirred and mixed at 600 r / min for 20 min to obtain an environmentally friendly anti-seepage and anti-pressure polymer coating for water conservancy.

[0023] Example 8 A water conservancy-specific environmentally friendly anti-seepage and anti-pressure polymer coating, comprising the following raw materials in parts by weight: 45 parts of organosilicon-modified epoxy resin, 30 parts of reactive diluent, 10 parts of modified glass flakes, 8 parts of modified nitrile rubber, 0.3 parts of defoaming agent, 0.5 parts of leveling agent, 1 part of dispersant, and 2 parts of pigment; The active diluent is allyl glycidyl ether; the defoamer is silicone defoamer DF-102 (supplier: Dongguan Defeng Defoamer Co., Ltd.); the leveling agent is polyacrylate leveling agent BYK358N; the dispersant is sodium dodecyl sulfate; the pigment is chrome yellow; The preparation of the environmentally friendly anti-seepage and anti-pressure polymer coating for water conservancy includes the following steps: The silicone-modified epoxy resin and the active diluent are stirred and mixed at 500 r / min for 8 min, then the speed is reduced to 100 r / min and a defoamer, a leveling agent, a dispersant and a pigment are added, and the mixture is stirred and mixed at 500 r / min for 8 min. Then the speed is reduced to 200 r / min and the modified glass flakes obtained in Example 2 are added, and the mixture is stirred and mixed at 900 r / min for 40 min. Then the speed is reduced to 200 r / min and the modified nitrile rubber obtained in Example 5 is added, and the mixture is stirred and mixed at 600 r / min for 25 min to obtain an environmentally friendly anti-seepage and anti-pressure polymer coating for water conservancy.

[0024] Example 9 A water conservancy-specific environmentally friendly anti-seepage and anti-pressure polymer coating, comprising the following raw materials in parts by weight: 50 parts of silicone-modified epoxy resin, 40 parts of reactive diluent, 15 parts of modified glass flakes, 10 parts of modified nitrile rubber, 0.5 parts of defoaming agent, 1.0 parts of leveling agent, 2 parts of dispersant, and 3 parts of pigment; The active diluent is butyl glycidyl ether; the defoamer is silicone defoamer DF-102 (supplier: Dongguan Defeng Defoamer Co., Ltd.); the leveling agent is polyacrylate leveling agent BYK358N; the dispersant is sodium dodecyl sulfate; the pigment is ultramarine; The preparation of the environmentally friendly anti-seepage and anti-pressure polymer coating for water conservancy includes the following steps: The organosilicon-modified epoxy resin and the active diluent are stirred and mixed at 600 r / min for 10 min, then the speed is reduced to 200 r / min and a defoamer, a leveling agent, a dispersant and a pigment are added, and the mixture is stirred and mixed at 600 r / min for 10 min. Then the speed is reduced to 300 r / min and the modified glass flakes obtained in Example 3 are added, and the mixture is stirred and mixed at 1000 r / min for 45 min. Then the speed is reduced to 300 r / min and the modified nitrile rubber obtained in Example 6 is added, and the mixture is stirred and mixed at 700 r / min for 30 min to obtain an environmentally friendly anti-seepage and anti-pressure polymer coating for water conservancy.

[0025] Comparative Example 1 Compared with Example 9, the modified glass flakes are replaced with ordinary glass flakes, that is, the glass flakes are not modified, and the rest is exactly the same as Example 9, to obtain an environmentally friendly anti-seepage and pressure-resistant polymer coating for water conservancy.

[0026] Comparative Example 2 Compared with Example 9, the modified glass flakes are replaced by adding product 1 and benzotriazole, that is, benzotriazole is not loaded in the glass flakes, and the rest is exactly the same as Example 9, to obtain an environmentally friendly anti-seepage and pressure-resistant polymer coating for water conservancy.

[0027] Preparation process of product 1: glass flakes (supplier: Lingshou County Laipeng Mineral Products Business Department, 40 mesh), xylene, and stannous octoate are stirred and mixed at room temperature for 40 minutes to prepare solution 2; then hexamethylene diisocyanate is added to xylene and ultrasonically dispersed for 20 minutes, and then added dropwise to solution 2 through a constant pressure dropping funnel in a nitrogen atmosphere, and then stirred and reacted at 150°C for 5 hours to obtain activated glass flakes; then the activated glass flakes and N-ethylaniline are added to ethyl acetate, Stir at room temperature for 3 hours to obtain product 1; in solution 2, the dosage ratio of glass flakes, xylene and stannous octoate is 23g:320mL:0.07g; the dosage ratio of hexamethylene diisocyanate, xylene and solution 2 is 12g:120mL:365mL; ​​the dosage ratio of activated glass flakes, N-ethylaniline and ethyl acetate is 17g:14g:85mL; glass flakes and xylene are used after dehydration, and the dehydration method is the same as step A1 of Example 3.

[0028] Comparative Example 3 Compared with Example 9, 4-amino-N,N-dimethyl-3-nitroaniline is replaced with 2-amino-4-nitrotoluene, that is, no tertiary amine is introduced, and the rest is exactly the same as Example 9 to obtain an environmentally friendly anti-seepage and pressure-resistant polymer coating for water conservancy.

[0029] Comparative Example 4 Compared with Example 9, 2,5-thiophenedicarboxylic acid is replaced with succinic acid, and 10 parts of 3-methylthiophene are added at the same time, that is, the thiophene ring is not grafted into the nitrile rubber. The rest is exactly the same as Example 9, and an environmentally friendly anti-seepage and anti-pressure polymer coating for water conservancy is obtained.

[0030] The following is a further effect test on the environmentally friendly anti-seepage and anti-pressure polymer coating for water conservancy prepared by the present invention, and the test results are as follows.

[0031] The coatings obtained in Examples 7-9 and Comparative Examples 1-4 were applied on a steel plate substrate, and the sample coatings were obtained after drying. The salt spray resistance performance test of the sample coatings was carried out according to the method specified in GB / T1771-2007 to evaluate the corrosion resistance of the coatings; the coating impermeability test was carried out on the sample coatings to determine the impermeability pressure, so as to evaluate the impermeability and pressure resistance of the coatings; the coatings obtained in Examples 7-9 and Comparative Examples 1-4 were applied on a steel plate substrate, and the surface drying time was measured. The surface drying time is the time when the coating disappears when the surface is touched with a finger during the curing process in the atmospheric environment, and the curing rate of the coating is evaluated. The test environment conditions are room temperature 25°C and humidity 40%; the sample coatings were subjected to artificial climate aging experiments with reference to GB / T23987-2009 to observe the changes in the coatings; the test results are recorded in Table 1;

[0032] According to the data in Table 1, the water conservancy special environmentally friendly anti-seepage and anti-compression polymer coating of the present invention has excellent corrosion resistance, anti-seepage and pressure resistance, weather resistance, and fast curing rate. It can be seen from Example 9 compared with Comparative Example 1 that only unmodified glass flakes are used, the bonding force of glass flakes and epoxy resin is insufficient, the anti-seepage and pressure resistance of the coating decreases, and benzotriazole is not introduced, and the salt spray resistance of the coating decreases, indicating that the corrosion resistance of the coating decreases. It can be seen from Example 9 compared with Comparative Example 2 that product 1 and benzotriazole are used, and the glass flakes in product 1 are modified and improved in bonding force with epoxy resin, but benzotriazole is not loaded in glass flakes, and benzotriazole is easily migrated and failed in the coating, and the stability is insufficient, resulting in a slight decrease in the salt spray resistance of the coating, indicating that the corrosion resistance of the coating decreases slightly. Comparison between Example 9 and Comparative Example 3 shows that no tertiary amine is introduced into the modified nitrile rubber, and the catalytic promotion effect on the aromatic primary amine-cured epoxy resin cannot be produced, and the surface drying time of the coating is prolonged, indicating that the curing rate of the coating is slowed down. Comparison between Example 9 and Comparative Example 4 shows that the thiophene ring is not loaded in the modified nitrile rubber, and direct addition and use are prone to migration failure, and the UV aging resistance of the coating cannot be effectively improved, resulting in a decrease in the weather resistance of the coating.

[0033] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A water conservancy-specific environmentally friendly anti-seepage and pressure-resistant polymer coating, characterized in that: The invention comprises the following raw materials in parts by weight: 40-50 parts of organosilicon-modified epoxy resin, 30-40 parts of reactive diluent, 10-15 parts of modified glass flakes, 8-10 parts of modified nitrile rubber, 0.3-0.5 parts of defoaming agent, 0.5-1.0 parts of leveling agent, 1-2 parts of dispersant and 2-3 parts of pigment; The preparation of the modified glass flakes comprises the following steps: Step A1: glass flakes, xylene, and stannous octoate are stirred and mixed at room temperature to obtain solution 1; diisocyanate is then added to xylene and ultrasonically dispersed, and then added dropwise to solution 1 through a constant pressure dropping funnel in a protective gas atmosphere, and stirred to react to obtain surface-activated glass flakes; then the surface-activated glass flakes and nitro-containing benzotriazole are added to ethyl acetate, and stirred to react to obtain a nitro product; Step A2: adding the nitro product to toluene, adding sodium dithionite with stirring, and then refluxing and stirring to react to obtain the amino product; Step A3: Add the amino product and potassium carbonate to dimethyl sulfoxide and stir to obtain a mixture 1, then add lauroyl chloride to dimethyl sulfoxide and stir to obtain a mixture 2, and add the mixture 2 dropwise to the mixture 1 under an ice-water bath, and stir to react to obtain modified glass flakes.

2. The environmentally friendly anti-seepage and anti-pressure polymer coating for water conservancy according to claim 1, characterized in that: The active diluent is selected from one of phenyl glycidyl ether, allyl glycidyl ether and butyl glycidyl ether; the defoamer is an organosilicon defoamer; the leveling agent is a polyacrylate leveling agent; the dispersant is sodium dodecyl sulfate; and the pigment is selected from one of titanium dioxide, chrome yellow, iron red and ultramarine.

3. The environmentally friendly anti-seepage and anti-pressure polymer coating for water conservancy according to claim 1, characterized in that: In step A1, the amount ratio of glass flakes, xylene and stannous octoate in solution 1 is 20-23g:300-320mL:0.05-0.07g; the diisocyanate is hexamethylene diisocyanate, and the amount ratio of diisocyanate, xylene and solution 1 is 10-12g:100-120mL:355-365mL; ​​the nitro-containing benzotriazole is 4-nitro-1H-1,2,3-benzotriazole, and the amount ratio of surface-activated glass flakes, nitro-containing benzotriazole and ethyl acetate is 15-17g:20-23g:75-85mL.

4. The environmentally friendly anti-seepage and anti-pressure polymer coating for water conservancy according to claim 1, characterized in that: In step A2, the dosage ratio of the nitro product, toluene and sodium dithionite is 18-20 g: 80-90 mL: 12-14 g; in step A3, the dosage ratio of the amino product, potassium carbonate and dimethyl sulfoxide in the mixed solution 1 is 6-8 g: 0.5-1.0 g: 40-50 mL; the dosage ratio of lauroyl chloride and dimethyl sulfoxide in the mixed solution 2 is 5.5-6.5 g: 20-30 mL; the dosage ratio of the mixed solution 1 and the mixed solution 2 is 50-60 mL: 25-35 mL.

5. The environmentally friendly anti-seepage and anti-pressure polymer coating for water conservancy according to claim 1, characterized in that: The modified nitrile rubber is prepared by the following steps: Step B1: Add 4-amino-N,N-dimethyl-3-nitroaniline and potassium carbonate to dimethyl sulfoxide and stir to obtain a mixed solution a, then add 4-pentenoyl chloride to dimethyl sulfoxide and stir to obtain a mixed solution b, and dropwise add the mixed solution b to the mixed solution a in an ice-water bath. After the dropwise addition is completed, the temperature is raised to 40-45° C., the reaction is stirred for 8-10 hours, and the double bond product is obtained by distillation under reduced pressure; Step B2: Add the double bond product to dichloromethane, stir for 30-40 minutes, then add 3-chloroperoxybenzoic acid, stir and react at room temperature for 5-6 hours to obtain an epoxy product; in a protective gas atmosphere, add 2,5-thiophene dicarboxylic acid to toluene, heat to 50-60°C, add pyridine, start stirring, then add the epoxy product, stir and react for 10-12 hours, then heat to 110-120°C, stir for 1-2 hours to obtain a hydroxyl product; Step B3: Add carboxylated nitrile rubber to DMF, add thionyl chloride under stirring, and reflux and stir at 50-60° C. for 6-8 hours to obtain an acyl chloride product; The hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide are stirred and mixed to obtain a mixed solution c; the acyl chloride product is added to dimethyl sulfoxide to obtain a mixed solution d, and the mixed solution d is slowly added dropwise to the mixed solution c in an ice water bath. After the addition is completed, the temperature is raised to 40-45°C, and the mixture is stirred at a constant temperature for 8-10 hours, and then the temperature is raised to 100-110°C, and the stirring is continued for 1-2 hours, and the nitro product is obtained by distillation under reduced pressure; Step B4: Add the nitro product to toluene, raise the temperature to 50-60°C, start reflux stirring, then add sodium dithionite, and reflux stirring to react for 3-3.5 hours to obtain modified nitrile rubber.

6. The environmentally friendly anti-seepage and anti-pressure polymer coating for water conservancy according to claim 5, characterized in that: In step B1, the dosage ratio of 4-amino-N,N-dimethyl-3-nitroaniline, potassium carbonate and dimethyl sulfoxide in the mixed solution a is 0.1-0.15 mol: 0.02-0.04 mol: 70-80 mL; the dosage ratio of 4-pentenoyl chloride and dimethyl sulfoxide in the mixed solution b is 0.15-0.17 mol: 30-40 mL; the dosage ratio of the mixed solution a and the mixed solution b is 75-85 mL: 40-50 mL.

7. The environmentally friendly anti-seepage and anti-pressure polymer coating for water conservancy according to claim 5, characterized in that: In step B2, the usage ratio of the double bond product, dichloromethane, and 3-chloroperoxybenzoic acid is 30-32 g: 80-90 mL: 18-20 g; the usage ratio of 2,5-thiophenedicarboxylic acid, toluene, pyridine, and epoxy product is 20-23 g: 180-200 mL: 0.2-0.25 mol: 68-70 g.

8. The environmentally friendly anti-seepage and anti-pressure polymer coating for water conservancy according to claim 5, characterized in that: In step B3, the amount ratio of carboxylated nitrile rubber, DMF and dichlorothionyl is 36-40g: 100-110mL: 12-14g; the amount ratio of hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide in mixed solution c is 88-90g: 4-6mL: 15-20mL: 160-170mL; the amount ratio of acyl chloride product and dimethyl sulfoxide in mixed solution d is 42-44g: 90-100mL; the amount ratio of mixed solution c and mixed solution d is 170-180mL: 100-110mL.

9. The environmentally friendly anti-seepage and anti-pressure polymer coating for water conservancy according to claim 5, characterized in that: In step B4, the usage ratio of nitro product, toluene and sodium dithionite is 65-70 g: 200-210 mL: 35-37 g.

10. A method for preparing the environmentally friendly anti-seepage and anti-pressure polymer coating for water conservancy according to any one of claims 1 to 9, characterized in that: The steps include: The organosilicon-modified epoxy resin and the active diluent are stirred and mixed at 500-600 r / min for 5-10 min, and then the speed is reduced to 100-200 r / min, and a defoamer, a leveling agent, a dispersant and a pigment are added, and the mixture is stirred and mixed at 500-600 r / min for 5-10 min, and then the speed is reduced to 200-300 r / min, and modified glass flakes are added, and the mixture is stirred and mixed at 800-1000 r / min for 35-45 min, and then the speed is reduced to 200-300 r / min, and modified nitrile rubber is added, and the mixture is stirred and mixed at 600-700 r / min for 20-30 min to obtain an environmentally friendly anti-seepage and anti-pressure polymer coating for water conservancy.

Citation Information

Cited By

  • High-weather-resistant anticorrosive epoxy resin coating and preparation method thereof

    CN119859455A